2020
DOI: 10.1111/aej.12449
|View full text |Cite
|
Sign up to set email alerts
|

A survey of current trends in root canal treatment: access cavity design and cleaning and shaping practices

Abstract: The purpose of this study was to evaluate current trends in access cavity design and cleaning and shaping among endodontists. A survey was e‐mailed to active members of the American Association of Endodontists. Data showed that most respondents used traditional (57%) or conservative (43%) access cavities; less than 1% reported using ultraconservative access cavities. A glide path was created by 93% of respondents; NaOCl was used as lubricant by 51% of respondents, while 28% used RC Prep, 9% used liquid EDTA, 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 31 publications
(36 reference statements)
3
10
0
Order By: Relevance
“…Close to the time of the survey, 180 endodontists were registered in Australia (AIHW, 2022), giving a representative response rate in this group of 37.2%. From the AAE mailing list, 463 responses were received giving an actual response rate of 8.3%, very similar to another recently published survey (Martinho & Griffin, 2021) but lower than 23%-24% achieved by others (Logsdon et al, 2020;Tsotsis et al, 2021). The proportion of female respondents in this study at 22% was lower than 34.4% reported in one recent international survey of endodontists (Galicia et al, 2021) but similar to 20%-21% reported in recent surveys of members of the American Association of Endodontists (Lin et al, 2015;Tsotsis et al, 2021).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Close to the time of the survey, 180 endodontists were registered in Australia (AIHW, 2022), giving a representative response rate in this group of 37.2%. From the AAE mailing list, 463 responses were received giving an actual response rate of 8.3%, very similar to another recently published survey (Martinho & Griffin, 2021) but lower than 23%-24% achieved by others (Logsdon et al, 2020;Tsotsis et al, 2021). The proportion of female respondents in this study at 22% was lower than 34.4% reported in one recent international survey of endodontists (Galicia et al, 2021) but similar to 20%-21% reported in recent surveys of members of the American Association of Endodontists (Lin et al, 2015;Tsotsis et al, 2021).…”
Section: Discussionsupporting
confidence: 77%
“…A few surveys exploring endodontists' overall clinical preferences have previously been published (Ferreira et al, 2017; Kohli et al, 2014; Rajbhandari et al, 2018). Other studies have investigated endodontists' preferences in specific areas such as single‐visit versus multiple‐visit treatment (Inamoto et al, 2002; Sathorn et al, 2009), surgical trends (Creasy et al, 2009), regenerative endodontic procedures (Epelman et al, 2009; Lee et al, 2018), dental operating microscope (Kersten et al, 2008; Mines et al, 1999), CBCT (Krug et al, 2019; Setzer et al, 2017), disinfection protocols (Clarkson et al, 2003; de Gregorio et al, 2015; Dutner et al, 2012), use of nickel–titanium instruments (Bird et al, 2009; Logsdon et al, 2020; Parashos & Messer, 2004), and access cavity and instrumentation (Tsotsis et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Since different designs of the MIE cavity have been proposed, many practitioners have already begun to apply them in clinical practice [ 2 , 19 , 20 ]. Previous studies have reported conflicting results regarding the influence of cavities on the fracture resistance of ETT.…”
Section: Discussionmentioning
confidence: 99%
“…In the clinic, most practitioners prepare CECs with a combination of dentists’ experience and the results of cone bone computed tomography scans. [ 20 ] It is inevitable that more PCD and dentin in the pulp chamber roof will be removed in CECs, which will weaken the fracture resistance of ETT with CECs.…”
Section: Discussionmentioning
confidence: 99%
“…The electronic measurement of working length with hand files involves attaching the EAL file holder above the stopper on the metal shank of the instrument. A recent survey of practicing endodontists in the United States showed that a majority of clinicians use hand files to establish working length as a glide path (19). Subsequent shaping of the canal influences the outcome of irrigation, filling and success of the root canal therapy (20).…”
Section: Introductionmentioning
confidence: 99%